2018
DOI: 10.1097/brs.0000000000002622
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Low-Speed Rear Impact Volunteer Studies and a Comparison to Real-World Outcomes

Abstract: Study Design.This study combined all prior research involving human volunteers in low-speed rear-end impacts and performed a comparative analysis of real-world crashes using the National Automotive Sampling System – Crashworthiness Data System.Objective.The aim of this study was to assess the rates of neck pain between volunteer and real-world collisions as well as the likelihood of an injury beyond symptoms as a function of impact severity and occupant characteristics in real-world collisions.Summary of Backg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Low speed or minimal damage rear impact crashes can be generally categorized as collisions with a delta V of <13 km/h (8 mph), as significant vehicle damage is unusual below this speed change in bumper to bumper impacts [ 20 ]. The risk of injury from such crashes has been described in the literature as ranging variously from a low of 12% (for <8 km/h [5 mph] delta V) to 47% for an 11 km/h (7 mph) delta V [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low speed or minimal damage rear impact crashes can be generally categorized as collisions with a delta V of <13 km/h (8 mph), as significant vehicle damage is unusual below this speed change in bumper to bumper impacts [ 20 ]. The risk of injury from such crashes has been described in the literature as ranging variously from a low of 12% (for <8 km/h [5 mph] delta V) to 47% for an 11 km/h (7 mph) delta V [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most recently (2018), Cormier and colleagues (all employees of Biodynamic Research Corporation), described a review of crash testing literature and an analysis of national crash injury data pertaining to rear impact crashes, noting that the latter indicated a 12% and 22% rate of cervical spine injury at <8 km/h and 8–16 km/h, respectively [ 60 ]. Despite this finding, the authors discussed the similarity between the forces of ADLs and the crashes, and concluded that an 18 km/h rear impact crash test is a safe event.…”
Section: Discussionmentioning
confidence: 99%
“…In MVCs, the vehicle's impact-related change in velocity is known as the delta-V (Dv), a quantity that is widely accepted as a general estimate of impact severity (72,73). Another key concept is the principal direction of force (PDOF) and typically is referenced to a horizontal clock face oriented at the impact location ( Figure 2).…”
Section: Underlying Biomechanical Principlesmentioning
confidence: 99%
“…It should be noted that the ideal design solution for anthropometric dummies intended for crash tests would be a design that would not require frequent calibration and at the same time ensure the durability of the joint and the repeatability of the results [28][29][30].…”
Section: Introductionmentioning
confidence: 99%